2003
DOI: 10.1046/j.1471-4159.2003.01587.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and immunohistochemical characterization of the APJ receptor and its endogenous ligand apelin

Abstract: Apelin peptides have recently been identified to be the endogenous ligands for the G protein-coupled receptor APJ. However, little is known about the physiological roles of this ligand-receptor pairing. In the present study we investigated the pharmacology of several apelin analogues at the human recombinant APJ receptor using radioligand binding and functional assays. This has led to the identification of key residues in the apelin peptide required for functional potency and binding affinity through structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
477
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(523 citation statements)
references
References 23 publications
28
477
1
3
Order By: Relevance
“…Low apj mRNA expression has previously been shown in human pancreas but it was not detected in rat pancreas (11). A possible species difference could account for this discrepancy, or it could be due to a dilution effect when the expression was studied in whole pancreas, since it is possible that the apj receptor only is expressed in islet cells.…”
Section: Insulin Secretion and Glucose Oxidation In Vitromentioning
confidence: 91%
See 1 more Smart Citation
“…Low apj mRNA expression has previously been shown in human pancreas but it was not detected in rat pancreas (11). A possible species difference could account for this discrepancy, or it could be due to a dilution effect when the expression was studied in whole pancreas, since it is possible that the apj receptor only is expressed in islet cells.…”
Section: Insulin Secretion and Glucose Oxidation In Vitromentioning
confidence: 91%
“…The endogenous ligand for the apj receptor is apelin, which was initially demonstrated in stomach extracts in 1998 (8). Later studies have shown that apelin mRNA is expressed in several tissues, as for example in several regions in the CNS, in the heart, lung, placenta, mammary gland and gastrointestinal tract (3,5,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, apelin and APJ mRNA transcripts and respective peptides, are abundantly present in central nervous system and also in peripheral tissues such as vascular endothelium, heart, lung, kidney and mammary gland [18,25,40,32,10,21], suggesting a functional role of apelin/APJ in these tissues. Remarkably the bulk of the studies report cardiovascular actions of apelin/APJ.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the endogenous ligand of APJ was identified from bovine stomach, and this peptide was named apelin (for APJ endogenous ligand) (2). APJ and apelin are expressed in several tissues including the cardiovascular and the central nervous systems (3)(4)(5)(6), and the structure of APJ and apelin is highly conserved among species, suggesting its important physiological roles.…”
mentioning
confidence: 99%